1996
DOI: 10.1128/jvi.70.6.3461-3469.1996
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the susceptibility of herpes simplex virus types 1 and 2 to modified heparin compounds suggest serotype differences in viral entry

Abstract: Although heparan sulfate (HS) serves as an initial receptor for the binding of both herpes simplex virus type 1 (HSV-1) and HSV-2 to cell surfaces, the two serotypes differ in epidemiology, cell tropism, and ability to compete for viral receptors in vitro. These observations are not necessarily contradictory and can be explained if the two serotypes recognize different structural features of HS. To compare the specific features of HS important for the binding and infection of HSV-1 and HSV-2, we took advantage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(39 citation statements)
references
References 63 publications
3
36
0
Order By: Relevance
“…Another interesting property of 3-OS HS is that HSV-2 gD fails to use it as a receptor for entry [7]. Indeed, even for the attachment process, HSV-2 demonstrates many differences in the HS structure recognition than HSV-1 [33]. It remains to be determined whether the inability to use 3-OS HS and additional differences in HS binding may have a role in the tissue tropism shown by the two HSV serotypes.…”
Section: Cellular Receptors For Gdmentioning
confidence: 99%
“…Another interesting property of 3-OS HS is that HSV-2 gD fails to use it as a receptor for entry [7]. Indeed, even for the attachment process, HSV-2 demonstrates many differences in the HS structure recognition than HSV-1 [33]. It remains to be determined whether the inability to use 3-OS HS and additional differences in HS binding may have a role in the tissue tropism shown by the two HSV serotypes.…”
Section: Cellular Receptors For Gdmentioning
confidence: 99%
“…For example, recent studies about the role of HS in assisting HSV-1 infections suggest that highly sulfated HS interacts with viral glycoprotein C and glycoprotein B, and is essential for the binding of virus to cells. 11,12 It has also been observed that a specific 3-O-sulfated HS interacts with viral glycoprotein D, which is critical for viral entry. These results suggest that the saccharide structures of HS have different activities in promoting viral infections, and understanding the structural specificity for viral infections is essential for antiviral drug development.…”
Section: Other Viruses Adenovirusmentioning
confidence: 99%
“…13,14 In addition, such structural variations of HS might provide the tissue-specificity for the viral bindings as suggested by the recently published results on herpes simplex viral attachment and infection. 11,12 However, unlike proteins or DNA, structural analysis of HS is very difficult as there are no general methods for characterizing these molecules. Combining the techniques from virology, carbohydrate biochemistry, molecular biology/genetics, and mass spectrometry, it becomes possible to rapidly investigate the specific roles of HS in assisting viral infections.…”
Section: Other Viruses Adenovirusmentioning
confidence: 99%
See 1 more Smart Citation
“…This has already been proposed for the treatment of both hepatitis C (He et al, 2015) and Ebola virus (Sakurai et al, 2015) infections. Heparin, the widely used anticoagulant, has potentially attractive features including activity against attachment and entry of the enveloped viruses, human simplex (HSV) (Herold et al, 1996;Nahmias and Kibrick, 1964), human immunodeficiency (HIV) (Baba et al, 1988), SARS coronavirus (Vicenzi et al, 2004), and influenza (H5N1) . Here, we explore the effects of heparin on ZIKV infection in human neural progenitor cells (hNPCs) with particular regard to virus replication and induction of cytopathic effects (CPE) resulting in cell death.…”
Section: Introductionmentioning
confidence: 99%